Association Between Air Pollutants and Pediatric Respiratory Outpatient Visits in Zhoushan, China - Liu, Wen-Yi; Yi, Jing-Ping; Shi, Leiyu; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Objective This study aimed to explore the time-series relationship between air pollutants and the number of children's respiratory outpatient visits in coastal cities. Methods We used time series analysis to investigate the association between air pollution levels and pediatric respiratory outpatient visits in Zhoushan city, China. The population was selected from children aged 0–18 who had been in pediatric respiratory clinics for eight consecutive years from 2014 to 2020. After describing the population and weather characteristics, a lag model was used to explore the relationship between outpatient visits and air pollution. Results We recorded annual outpatient visits for different respiratory diseases in children. The best synergy lag model found a 10 μg/m3 increase in PM2.5 for every 4–10% increase in the number of pediatric respiratory outpatient visits (P < 0.05). The cumulative effect of an increase in the number of daily pediatric respiratory clinics with a lag of 1–7 days was the best model. Conclusions PM2.5 is significantly related to the number of respiratory outpatient visits of children, which can aid in formulating policies for health resource allocation and health risk assessment strategies.